Reattachment of Coronal Tooth Fragment: Regaining Back to Normal - B. Vishwanath; Umrana Faizudin; M. Jayadev; Sushma Shravani (Case Reports in Dentistry)
Dental trauma is such a situation wherein the patient is affected both socially and psychologically. During their first dental visit, these patients with trauma are in pain and need emergency treatment. Such patients are quite apprehensive because of impaired functions, esthetics, and phonetics. The prime objective while handling such cases is successful pain management with immediate restoration of function, esthetics, and phonetics. The advances in adhesive dentistry have allowed dentists to use the patient’s own fragment to restore the fractured tooth. Reattachment is such an ultraconservative technique which provides safe, fast, and esthetically pleasing results. This paper discusses fragment reattachment technique and presents a clinical case of complicated crown fracture.